Penerapan Teknik Storytelling Influencer pada Konten Strategi Branding UMKM Fashion - Made Ruchita Wardani; Ni Putu Intan Permatasari (VISA: Journal of Vision and Ideas, 2026)
The rapid development of information and communication technology has brought significant changes in marketing strategies, particularly through social media platforms like tiktok, which increasingly become the primary choice for smes to reach broad markets efficiently. This thesis aims to analyze the storytelling techniques employed by influencers as a branding strategy for ellizeshoes on tiktok. The research questions focus on how storytelling techniques are used to shape brand perception and their effectiveness in increasing audience engagement. A qualitative descriptive approach with data collection methods such as in-depth interviews, observation, and document analysis was employed, along with source and technique triangulation to ensure data validity. The findings reveal that influencer storytelling successfully builds an appealing and relevant brand image, enhances positive perception, and fosters consumer trust toward ellizeshoes. This strategy proved effective in increasing brand awareness and audience engagement on tiktok. The study provides valuable insights into digital marketing strategies based on influencer marketing and storytelling within the local fashion industry.